THE EFFECTIVENESS OF COGNITIVE RESTRUCTURING TECHNIQUES TO IMPROVE CAREER DECISION-MAKING SELF-EFFICACY - Kade Sathya Gita Rismawan Rismawan; Luh Asli; Ini Wayan Monik Rismadewi (RADJA PUBLIKA, 2026)
This present study aims at investigating the effectiveness of cognitive behavioral counseling through cognitive restructuring to improve students' career decision making self-efficacy. This study employs a single subject research with multiple baselines across subjects design. There are three students from twelfth graders in SMA Lab Undiksha involved in this study. In order to gather the data, the researcher utilizes career decision making self-efficacy scale and ideas sheet. Further, the data are analyzed visually which cover under condition analysis and between condition analysis. According to, this study shows that students are able to improve their career decision making self-efficacy on intervention phase. This reflects that cognitive behavioral counseling through cognitive restructuring effectively improves students' career decision making self-efficacy. Thus, this study implies both the theoretical and practical perspectives of the effort to improve students' career decision making self-efficacy.